1999
DOI: 10.1042/0264-6021:3390397
|View full text |Cite
|
Sign up to set email alerts
|

N-glycosylation requirements for the AT1a angiotensin II receptor delivery to the plasma membrane

Abstract: The purpose of this work was to investigate the role of N-glycosylation in the expression and pharmacological properties of the the rat AT1a angiotensin II (AII) receptor. Glycosylation-site suppression was carried out by site-directed mutagenesis (Asn-->Gln) of Asn176 and Asn188 (located on the second extracellular loop) and by the removal of Asn4 at the N-terminal end combined with the replacement of the first four amino acids by a 10 amino acid peptide epitope (c-Myc). We generated seven possible N-glycosyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 35 publications
3
12
1
Order By: Relevance
“…The AT 1 R has also been shown to undergo post-translational glycosylation 31 and the glycosylated AT 1 R is predicted to have a higher molecular weight. 33 In the present study rat kidney (used as a positive control) showed the ≈58 kDa glycosylated band, consistent with previous reports 34 and this higher molecular weight band was also detected in the cultured cremaster myocytes (Figure S5A, Left Column). As an index of specificity Western blotting was performed after pre-treating the antibody with a blocking peptide/antigen-directed against the AT 1 R (Figure S5A, Right Column).…”
Section: Discussionsupporting
confidence: 93%
“…The AT 1 R has also been shown to undergo post-translational glycosylation 31 and the glycosylated AT 1 R is predicted to have a higher molecular weight. 33 In the present study rat kidney (used as a positive control) showed the ≈58 kDa glycosylated band, consistent with previous reports 34 and this higher molecular weight band was also detected in the cultured cremaster myocytes (Figure S5A, Left Column). As an index of specificity Western blotting was performed after pre-treating the antibody with a blocking peptide/antigen-directed against the AT 1 R (Figure S5A, Right Column).…”
Section: Discussionsupporting
confidence: 93%
“…N-glycosylation regulates GPCR structure and maturation [3436]. Consistent with the findings from Versano et al [26], a prominent broad band of LPA1-V5 at ~60 kDa was shifted to ~40 kDa after treatment with PNGase F, an endoglycosidase to remove N-linked glycans (Fig.…”
Section: Resultssupporting
confidence: 86%
“…A single band at ~51 kDa was present in all samples including the mock-transfected cells and likely represents endogenous His proteins expressed by HEK cells (marked with an asterisk on Fig 5b). Nevertheless, the ~39 kDa band is consistent with the non-glycosylated form of the AT 1 R 12 even though one may question the apparent molecular weight of AT 1 R “monomer” because this band appears to be slightly smaller than the predicted 41 kDa mass of this protein. This small apparent difference in size could be accounted for by an altered migration velocity due to the positively charged histidines added to the carboxyl-terminal tail.…”
Section: Discussionmentioning
confidence: 88%
“…Since both AT 1 R isoforms undergo post-translational glycosylation, a single ~41 kDa band should represent the non-glycosylated AT 1A or AT 1B receptor whereas higher molecular bands would be expected for the glycosylated forms. 12 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation